2006
DOI: 10.1080/17453670610012647
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a soft interface- (Proplast-) coated femoral stem

Abstract: Background Mid-term clinical results of uncemented femoral components with a Proplast coating have been unfavorable and the low modulus system was abandoned in the mid-1990s. There are, however, still substantial numbers of patients with a Proplast-coated prosthesis in situ. We evaluated the clinical and radiographic results in patients with 8-13 year follow-up.Methods We evaluated the survival rate, Harris Hip score and radiographic features of 82 hips in 69 patients. Mean age at operation was 58 (35-72) year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The low-modulus, porous surface layer was employed in the hopes that it would promote cementless fixation [159]. Unfortunately, the polymer coating led to unacceptably high loosening rates and was ultimately abandoned in the 1990s [160], but unfortunately not before it had been implanted in hundreds of patients.…”
Section: Femoral Stemsmentioning
confidence: 99%
“…The low-modulus, porous surface layer was employed in the hopes that it would promote cementless fixation [159]. Unfortunately, the polymer coating led to unacceptably high loosening rates and was ultimately abandoned in the 1990s [160], but unfortunately not before it had been implanted in hundreds of patients.…”
Section: Femoral Stemsmentioning
confidence: 99%
“…There is a paucity of modern literature regarding composite femoral stem component failure in primary THA. It has been previously demonstrated that the results of the soft interface proplast-coated femoral stem were unfavorable, with reports demonstrating high rates of aseptic loosening and osteolysis [5]. [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of modern literature regarding composite femoral stem component failure in primary THA. It has been previously demonstrated that the results of the soft interface proplast-coated femoral stem were unfavorable, with reports demonstrating high rates of aseptic loosening and osteolysis [5]. Clinical results have been relatively successful to this point for the Epoch composite stem, as with the intermediate-term follow-up of the femoral implant by Akhavan et al, who demonstrated improvement in average Harris hip scores (56 to 97), no instances of component migration, and only one hip with osteolysis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous composite stems made of polymer materials reinforced by a central metallic core, carbon fiber, or a flexible metallic construct were tried in a few studies [7,12,17,21,27,29,30,38,41,43,51,52] and also in revisions [25,31]. Even if some of these stems reduced postoperative loss of proximal femoral bone mineral density (BMD), most of them failed clinically as a result of poor fixation.…”
Section: Introductionmentioning
confidence: 99%